Grandilodines A—C, Biologically active indole alkaloids from kopsia grandifolia - Kam, T.S.; Yap, W.S.; Gan, C.Y.; Low, Y.Y.; Choo, Y.M.; Etoh, T.; Hayashi, M.; Komiyama, K. (American Chemical Society and American Society of Pharmacognosy, 2011)
Three new indole alkaloids (1—3), named grandilodines A—C, and five known ones were obtained from the Malayan Kopsia grandifolia. The structures were established usingNMRand MS analyses and, in the case of 1 and 2, were confirmed by X-ray diffraction analyses. Alkaloids 1, 3, and lapidilectine B (8) were found to reverse multidrug resistance in vincristine-resistant KB cells.